Application of the Delphi Method in the Study of Depressive Disorder - Wu, Hengjin; Xu, Linjie; Zheng, Yu; Shi, Lei; Zhai, Liangfan; Xu, FengQuan (Frontiers in Psychiatry, 2022)
Depressive disorder is a common mental disorder that has a high prevalence and low visiting rate, which caused patients years lived with disability. Due to the complexity of the depressive disorder, the Delphi method is a better choice compared with other commonly used methods, which provides a new perspective for the prevention and treatment of depression. This article will summarize the clinical studies of depressive disorders using the Delphi method from 4 perspectives, and summarize the advantages and disadvantages of the Delphi method in depressive disorders research, arguing that the Delphi method can cross the gap between clinical research and clinical practice, and is a highly practical part of the research process.